Analisis Self Determination Theory dalam Dinamika Kepemimpinan Kru Topi Jerami: Studi Kasus Film Anime “One Piece” - Ach Muzajjad; Betty Rahayu; Wina Nurhayati; Aslichah Aslichah (Journal of Indonesian Economic Research, 2026)
The purpose of this study is to examine the manifestation of Self Determination Theory (SDT) in the leadership dynamics of the Straw Hat Pirates in the anime One Piece, specifically how Monkey D. Luffy fulfills the needs for autonomy, competence, and relatedness with his teammates, and how this impacts their motivation and loyalty. The method used is an intrinsic case study design with a qualitative approach. This study analyzes six story arcs from 407 episodes using systematic thematic analysis based on the Self-Determination Theory framework. Data were collected through content analysis with clear operational criteria. Results indicate that Luffy's leadership consistently demonstrates autonomy support, competence development support, and deep relatedness cultivation, resulting in organismic integration, a condition where crew members internalize the collective mission as a crucial part of their personal identity. This pattern results in deep intrinsic motivation, transformative loyalty, spontaneous prosocial behaviors, and extreme resilience in adversity. Study limitations include challenges in generalizing findings from fictional narratives to real-life situations, absence of internal psychological data, and potential cultural bias in interpreting SDT constructs. Practical implications emphasize the importance of need-supportive leadership in modern organizations for developing human potential and maintaining high-performance teams.